Carbapenem Resistance in Non-Fermentative Gram-Negative Bacilli Isolated from Intensive Care Unit Patients of a Referral Hospital - Yadav, Santosh Kumar; Bhujel, Rajshree; Mishra, Shyam Kumar; Sharma, Sangita; Sherchand, Jeevan Bahadur (Journal of Nepal Health Research Council, 2021)
Background: Non-fermentative Gram-negative bacilli or non-fermenters are opportunistic pathogens associated with serious infections in intensive care unit patients. Although carbapenems were considered as a backbone of treatment for life-threatening infections, these bacteria are increasingly acquiring resistance to carbapenems. Carbapenem-resistant Acinetobacter baumannii and Pseudomonas aeruginosa are prioritized as critical pathogens by the World Health Organization. The objective of the study was to document the status of carbapenem-resistant and carbapenemase-producing non-fermenters isolated from intensive care unit patients.Methods: This study was conducted at Tribhuvan University Teaching Hospital, Kathmandu, Nepal. The clinical specimens collected from intensive care unit patients were processed for isolation and identification of non-fermenters and antibiotic susceptibility profile of bacterial isolates was determined. The multidrug-resistant isolates were identified and carbapenemase enzyme was detected in the carbapenem-resistant isolates.Results: A total of 157 non-fermenters were isolated from 1063 samples which included Acinetobacter species (n=85), Pseudomonas aeruginosa (n=55), Burkholderia cepacia complex (n=15), and Stenotrophomonas maltophilia (n=2). Carbapenem resistance was reported in 85.9%, 72.7%, and 33.3% of Acinetobacter species, Pseudomonas aeruginosa, and Burkholderia cepacia complex, respectively. Among total non-fermenters, 91.1% isolates were multidrug-resistant and 60.8% carbapenem-resistant isolates were carbapenemase producers. The carbapenem-resistant isolates demonstrated an extremely high degree of resistance than carbapenem-susceptible isolates towards other antimicrobial classes.Conclusions: This study reported high rates of carbapenem-resistant, carbapenemase-producing, and multidrug-resistant non-fermenters isolates. Therefore, preventing the spread of these superbugs among the critically ill patients in intensive care units should be a major initiative in hospitals.Keywords: Carbapenem-resistant; carbapenemase; intensive care unit; non-fermentative Gram-negative bacilli